The Concept of Justice According to Abdurrahman Wahid and Its Implications for Islamic Education - Elika Fadiah; Muhlas Muhlas; Maman Lukmanul hakim; Naan Naan (IQRO: Journal of Islamic Education, 2026)
This study examines the construction of the concept of justice in the thought of Abdurrahman Wahid (Gus Dur) and its implications for Islamic education as a response to the persistent problems of discrimination, intolerance, and exclusivism in contemporary Islamic educational practices. The novelty of this study lies in its analytical perspective, which positions justice not merely as a derivative value of Gus Dur's ideas on humanism and pluralism, but as an independent analytical category and an overarching principle that integrates humanism, equality, pluralism, democracy, and the protection of minority groups within a unified conceptual framework. This study employed a qualitative approach using a library research design. Data were collected through a systematic literature review of Gus Dur's primary works and relevant scholarly literature, while data analysis was conducted using content analysis combined with a philosophical and conceptual approach. The findings reveal that Gus Dur's concept of justice is epistemologically rooted in the ideas of the indigenization of Islam, Islamic universalism, and the rejection of defensive and exclusive forms of religiosity. Consequently, his understanding of justice is transformative in nature because it emphasizes structural correction of injustice rather than merely providing normative recognition of equality. Furthermore, this concept of justice has practical implications for six essential components of Islamic education, namely educational objectives, curriculum development, teacher-student relationships, learning processes, assessment systems, and educational culture. Theoretically, this study contributes to the development of contemporary Islamic thought by formulating a model of transformative justice-based Islamic education. Practically, it provides a conceptual reference for educators and educational policymakers seeking to develop Islamic education that is more humanistic, inclusive, democratic, and oriented toward the common good. Nevertheless, this study is limited by its reliance on textual analysis and does not include empirical verification within contemporary Islamic educational institutions.